Implementation of Employee Professional Competencies in Increasing Work Motivation at PT JNE Pati - Riesha, Riezky Army; Suprianto, Joko (Journal of Social Science, 2024)
Employees in logistics companies such as JNE play a crucial role in maintaining good operational performance. Employees with strong professional competencies can become valuable assets in responding to industry changes and demands. Therefore, the aim of this research is to examine the implementation of professional competencies among employees at PT JNE Pati. The research method utilized is a descriptive qualitative research approach. The findings indicate that the implementation of professional competencies at PT JNE Pati has a positive impact on employees' work motivation. Enhanced skills and knowledge through training, career development opportunities, the creation of a work environment that supports professional growth, performance evaluation, and the implementation of recognition policies contribute significantly to employees' enthusiasm and engagement.